Extent of losses and possibilities to optimize pest management in potato cropping systems in Kenya - Syndikus, K. (Universitat Hohenheim, 2010)
Potato is an important food and cash crop in the mid- and highlands of Kenya. The actual yidd however is far below its potential. The aim of the study was to assess the importance of potato production and its major constraints as perceived by the farmers. Further, the status of insect pests related to potato cultivation, and in particular leafminer fly and potato tuber moth were to be assessed. The study was carried out from September to December 2009 in five potato growing regions in Kenya. Beside household surveys, abundant insect pests were detected through trapping. The flight activity of leafminer fly, using yellow sticky traps, and of potato tuber moth, using pheromone traps, was regularly monitored. Regular field observations were carried out in two-weekly intervals to estimate the field infestation caused by both insect pests. Furthermore, the impact of potato tuber moth in storage was assessed. Through regular sampling of larvae, parasitoids associated with both leafminer fly and potato tuber moth were detected and their parasitisation estimated. Generally, potatoes are highly important for income generation and can be cultivated throughout the year. However, high costs of fertilizer and pesticides limit the potential outcome. Insect pests are not widely perceived as major constraint and are rarely controlled through chemicals. Insect diversity during the observation period was found to be relatively low. Aside from the low awareness of farmers, insect pests can cause considerable damage. Leafminer fly causes significant damage to potato crops in Abothuguci West, but is only either moderately or negligibly abundant in the other regions. All of the assessed regions showed field infestation by potato tuber moth. However, the situation is most serious in Naromoru. High infestation levels on seed tubers after storage were observed in Naromoru and Sagana. Aphids are widely distributed; however, bear the risk of virus transmission. A high variety of parasitoids for leafminer fly and potato tuber moth were found. The most important species for leafminer fly are Diglyphus spp., Gronotoma micromorpha and Opius spp., even though most of the species require further identification. Highest parasitisation rates of potato tuber moth were realized by Copidosoma koehleri and the indigenous Diadegma mollipla.